Lupus band test: diagnostic value in disseminated lupus erythematosus. - Carvalho, M F (1991)
By direct immunoflurescence, deposits of immunoglubins and complement were investigated at the dermal epidermal junction in skin specimens from 210 patients divided into three groups: A--134 patients without lupus; B--54 patients with Systemic Lupus Erythematosus (SLE); C--22 patients with Discoid Lupus Erythematosus. Twenty two patients from group B were submitted to renal biopsy: 20 of these demonstrated a positive lupus band test and data suggested a positive correlation between the intensity of immunoglobulin and complement deposition at the dermal epidermal junction with more severe renal involvement. The other 32 patients were not submitted to renal biopsy; in sediment and band test, may be of value in the prevision of patients with higher probability of developing more serious renal lesions. Our results revealed a high specificity (85.5%) and sensitivity (87%). Test positivity was uninfluenced by steroid and immunosuppressive therapy. The test appears to be of great interest for use on all patients who fail to meet the criteria for the diagnosis of SLE but whose condition suggest such a diagnosis.